New Criteria for Safety Distances During Pneumatic Pressure Testing of Vessels and Pipes. Issue 3 (7th December 2018) - Miller, Derek; Jallais, Simon; Pham‐Huy, Minh; Geng, Jihui
Abstract : The industrial gas and liquefied natural gas (LNG) industries routinely perform equipment pressure testing pneumatically, rather than hydraulically, due to the necessity for keep piping and equipment dry. Hazards associated with potential failure of pneumatically pressurized equipment under test are well understood, but today, there is no commonly recognized industry guidance on recommended safety distances to protect personnel during such tests. Air Products, Air Liquide and BakerRisk have worked together to develop such guidance for the testing of vessels, process pipes and pipelines, and present in this article new, simple to use correlations, with results also presented in the form of lookup tables. These new correlations are based on the application of established methods, validated against previously published independent test data and new test data presented here for the first time. © 2018 American Institute of Chemical Engineers Process Saf Prog 38: e12025, 2019